Colonialism, modernity, and religious identities : religious reform movements in South Asia - Beckerlegge, Gwilym editor (New Delhi : Oxford University Press, 2008)
Contributed articles; chiefly on Hindu and Muslim reform movements of India.
Based on presentations at the 17th European Conference on Modern South Asian Studies at Heidelberg in 2002.
Includes bibliographical references.
Keywords: Hindu renewal -- India -- Congresses; Hinduism -- India -- Congresses; Islamic renewal -- India -- Congresses; Islam -- India -- Congresses